Theory of isomeric excitation of 229Th via electronic processes - Zhang, Hanxu; Wang, Xu (Frontiers in Physics, 2023)
A unified theoretical framework is presented for the isomeric excitation of the ^229Th nucleus via electronic processes. These processes include nuclear excitation by electron transition (NEET), nuclear excitation by electron capture (NEEC), and nuclear excitation by inelastic electron scattering (NEIES). Detailed calculation results on the excitation rate and the excitation cross section are presented.